OLGA- and OLGIM-Based Staging in the Patients with Gastritis and Endoscopy Indications - Mansour-Ghanaei, Fariborz; Joukar, Farahnaz; Yeganeh, Sara; Sadeghi, Mahbobeh; Daryakar, Arash; Sepehrimanesh, Masood (Turkish Journal of Gastroenterology, 2022)
Background: Gastric cancer is one of the most common cancers with high mortality. In Iran, the high-risk regions include Northern andNorthwestern parts. The aim of this study was to assess the operative link on gastritis assessment- and operative link on gastric intestinal metaplasia-based staging in patients with upper gastrointestinal symptoms.Methods: Totally, 345 patients underwent upper gastrointestinal endoscopy. Also, the status of Helicobacter pylori infection was evaluated using rapid urease test and histological method. Moreover, histological changes were assessed using the Update Sydney System.The operative link on gastritis assessment- and operative link on gastric intestinal metaplasia-based stages of 0-II were considered aslow-risk stages and stages III and IV were considered as high-risk stages.Results: Most of the patients were lower than 60 years (245 patients, 71%), and 71.9% of our patients had H. pylori infection. Thefrequency of atrophic gastritis and intestinal metaplasia was 44.9% and 25.2%, respectively (P < .001). Eleven patients (73.7%) withgastric adenocarcinoma had a low risk and 2 patients with low-grade dysplasia had a high risk of operative link on gastritis assessmentand operative link on gastric intestinal metaplasia. Almost, 62.5% of gastric cancer patients with an intestinal type of gastric adenocarcinoma were at low-risk stages.Conclusions: Although high stages of operative link on gastritis assessment and operative link on gastric intestinal metaplasia needfurther follow-up, lower stages of atrophy or intestinal metaplasia also require follow-up. Furthermore, operative link on gastritis assessment method in detecting a greater number of patients who need follow-up is more successful and profitable.